Rv0100, a proposed acyl carrier protein in Mycobacterium tuberculosis: expression, purification and crystallization. Issue 10 (4th October 2019) - Bondoc, Jasper Marc G.; Gutka, Hiten J.; Almutairi, Mashal M.; Patwell, Ryan; Rutter, Maxwell W.; Wolf, Nina M.; Samudrala, Ram; Mehboob, Shahila; Movahedzadeh, Farahnaz
Abstract : Rv0100 is an essential acyl carrier protein for the pathogenesis and growth of Mycobacterium tuberculosis . Using Mycobacterium smegmatis as a host, Rv0100 was successfully cloned, purified and crystallized, and the crystals diffracted to 1.9 Å resolution. Abstract : Acyl carrier proteins (ACPs) are important components in fatty‐acid biosynthesis in prokaryotes. Rv0100 is predicted to be an essential ACP in Mycobacterium tuberculosis, the pathogen that is the causative agent of tuberculosis, and therefore has the potential to be a novel antituberculosis drug target. Here, the successful cloning and purification of Rv0100 using Mycobacterium smegmatis as a host is reported. Crystals of the purified protein were obtained that diffracted to a resolution of 1.9 Å. Overall, this work lays the foundation for the future pursuit of drug discovery and development against this potentially novel drug target.